LOCUS OF CONTROL SEBAGAI PEMODERASI PENGARUH PROFESIONALISME DAN KOMPLEKSITAS TUGAS PADA KINERJA AUDITOR - Gautama, Putu Krisna; Dwirandra, A.A.N.B. (E-Jurnal Akuntansi, 2017)
Performance auditors profesionaisme influenced by the level and complexity of the task faced by auditors. This study aims to examine the effect of locus of control as the moderating influence of professionalism and complexity of the task on the performance of auditors in public accounting office in Bali. This research was conducted on a public accounting firm in the area of ??Bali. Methods pengumpulann data using survey method with questionnaire technique, while the method of determining the non-probability sampling method sampelyaitu denganteknik purposive sampling. Data analysis are multiple regression and MRA. The results showed professionalism positive effect on the performance of auditors while the complexity of the task negative effect on the performance of auditors and locus of control able to moderate the influence of professionalism in the performance of auditors and locus of control is not able to moderate the effect of task complexity on the performance of auditors.
Keywords: professionalism; task complexity; locus of control; performance auditor